KEPUASAN KERJA, KOMITMEN ORGANISASIONAL, DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA KARYAWAN HOTEL BALI RELAXING RESORT & SPA, NUSA DU - Lasmi, Ni Wayan; Fungky, Ni Kadek May Fang Deliana (Jurnal Ilmiah Manajemen & Bisnis, 2018)
Job Satisfaction, Organizational Commitment, and Organizational Citizenship Behavior on Employee Performance of Hotel Bali Relaxing Resort & Spa, Nusa Dua.This study aims to determine the impact of job satisfaction, organizational commitment, and organizational citizenship behavior on employee performance. This research is conducted at Hotel Bali Relaxing Resort & Spa, Nusa Dua by using its employees, especially Room Attendants and Stewards as respondents. The number of respondents in this study are 35 employees, which 25 employees are Room Attendants and 10 employees are Stewards. The data analysis technique used is multiple linier regression analysis technique which are operated through the SPSS version 23.0 program. The results of the analysis show that job satisfaction has a positive and significant effect on employee performance, organizational commitment has a positive and significant effect on employee performance, and organizational citizenship behavior also has a positive and significant effect on employee performance. Based on the significant value of 0,000 < 0,50, means that there is a significant simultaneous influence between job satisfaction, organizational commitment, and organizational citizenship behavior on employee performance at the Hotel Bali Relaxing Resort & Spa, Nusa Dua especially in the Room Attendats and Stewards section. The coefficient of determination (Adjusted R square) in this study is 0,792 or 79,2%, means that the employee performance variables can be explained by the job satisfaction, organizational commitment, and organizational citizenship behavior variables. While the remaining 20,8% is explained by other variables not examined in this study. Keywords: job satisfaction, organizational commitment, organizational citizenship behavior, employee performance.